2021
DOI: 10.5222/bmj.2021.77200
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for 28-Day Mortality Among COVID-19 Patients in an Intensive Care Unit of a Tertiary Care Center in Istanbul

Abstract: Objective: In late 2019, the Coronavirus disease 2019 (COVID-19) has been pandemic worldwide, starting in Wuhan, China. In this study, we aimed to evaluate the factors associated with 28-day outcomes in patients admitted to the intensive care unit with the diagnosis of COVID-19. Methods: This study has a retrospective cohort design. COVID-19 patients identified according to World Health Organization guidelines are included. Patient data were recorded to a centralized system utilizing ImdSoft-Meta vision/QlinIC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Pneumonia, kidney damage, shock status, heart failure, and acute respiratory distress syndrome (ARDS) constitute the main clinical factors affecting COVID-19 mortality. In most patients laboratory parameters associated with COVID-19 mortality were reported as follows: leukocytosis, neutrophilia, elevated levels of alanine aminotransferase (ALT), and aspartate aminotransferase (AST), creatinine, lactate dehydrogenase (LDH), procalcitonin, C-reactive protein (CRP), N-terminal pro-brain natriuretic peptide (NT-proBNP), ferritin, D-dimer, lymphopenia, thrombocytopenia, along with decreased levels of albumin (7,8,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Pneumonia, kidney damage, shock status, heart failure, and acute respiratory distress syndrome (ARDS) constitute the main clinical factors affecting COVID-19 mortality. In most patients laboratory parameters associated with COVID-19 mortality were reported as follows: leukocytosis, neutrophilia, elevated levels of alanine aminotransferase (ALT), and aspartate aminotransferase (AST), creatinine, lactate dehydrogenase (LDH), procalcitonin, C-reactive protein (CRP), N-terminal pro-brain natriuretic peptide (NT-proBNP), ferritin, D-dimer, lymphopenia, thrombocytopenia, along with decreased levels of albumin (7,8,17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have been conducted on the level of acute phase reactants in COVID-19. In one study, it was reported that ESR, D-dimer, and procalcitonin levels increased significantly in severe cases [1] , [5] . In another study, ferritin and procalcitonin values were found to be high in non-surviving and severe COVID-19 patients.…”
Section: Discussionmentioning
confidence: 98%
“…In many studies, it has been stated that the levels of serum AST, ALT and LDH, which are liver function tests, were higher in severe COVID-19 patients when compared to the mild COVID-19 patients [1] , [5] , [21] . Onur et al [20] showed that the AST, ALT, and LDH activities were higher in deceased COVID-19 patients than in living patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations